Taxing Micro, Small and Medium Enterprises in Yogyakarta: Regulation and Compliance - Siti Rahma Novikasari; Duc Quang Ly; Kerry Gershaneck (BESTUUR, 2021)
The Special Region of Yogyakarta is a region with prominent Micro, Small, and Medium Enterprises (MSMEs) actors in Indonesia. This invites the important question of whether the implementation of the new MSMEs tax regulations in the region impacts the intensification of final income tax and tax compliance. This study aims to analyze the relationship between the amendments of the final income tax policy and the legal compliance of MSMEs taxpayers. This research uses a juridical and empirical approach. Empirical data was collected by interview and questionnaire to seven taxpayers, while juridical data was obtained by analyzing the Government Policy on taxation. This study shows that the reduction of the final income tax tariff from 1% to 0.5% and the existence of legal certainty regarding the taxation time frame implies a positive impact on taxpayer compliance. This is demonstrated by the fact that the number of taxpayers in 2019 increased by 15% when compared to 2017. However, tariff reduction is not the solution to the non-compliant taxpayer. The Regional Office of the Directorate General of Taxes still found the tax avoidance. It means the government needs to conduct a more cooperative approach to improve MSMEs taxpayer compliance.